Complete ADAMTS13 remission in a patient with refractory autoimmune-mediated thrombotic thrombocytopenic purpura after infliximab. (December 2021) - Bavli, Natalie; Lee, Nicholas; Sarode, Ravi; Burstein, Ezra; Rambally, Siayareh
Abstract: Autoimmune thrombotic thrombocytopenic purpura (aTTP) is caused by autoantibodies to the von Willebrand Factor cleaving enzyme, ADAMTS13. Despite recent advances in the treatment of acute aTTP, relapse rates remain high. Guidance for the treatment of patients in clinical remission but with persistent severe ADAMTS13 deficiency who fail to respond to rituximab remains unclear. We report a case of a 29-year-old man diagnosed with aTTP at the age of 11. Over a period of 18 years, he had five clinical relapses with persistent severe ADAMTS13 deficiency (<10%) and presence of autoantibodies during clinical remissions despite immunosuppressive therapy with rituximab, bortezomib and azathioprine. While in a clinical remission, he was diagnosed with Crohn's disease and initially treated with adalimumab. When he subsequently developed antibodies to adalimumab, he was transitioned to infliximab. ADAMTS13 activity increased to 24% by 2 months of infliximab induction, and four months later the ADAMTS13 activity improved to 42%. This case demonstrates the importance of managing concurrent inflammatory disorders and suggests that TNF may play a role in autoantibody development and ADAMTS13 depletion.